Root exudate analogues accelerate CO 2 and CH 4 production in tropical peat - Girkin, N.T.; Turner, B.L.; Ostle, N.; Craigon, J.; Sjögersten, Sofie (Elsevier, 2018)
Root exudates represent a large and labile carbon input in tropical peatlands, but their contribution to carbon dioxide (CO2) and methane (CH4) production remains poorly understood. Changes in species composition and productivity of peatland plant communities in response to global change could alter both inputs of exudates and associated greenhouse gas emissions. We used manipulative laboratory incubations to assess the extent to which root exudate quantity and chemical composition drives greenhouse gas emissions from tropical peatlands. Peat was sampled from beneath canopy palms (Raphia taedigera) and broadleaved evergreen trees (Campnosperma panamensis) in an ombrotrophic wetland in Panama. Root exudate analogues comprising a mixture of sugars and organic acids were added in solution to peats derived from both species, with CO2 and CH4 measured over time. CO2 and CH4 production increased under most treatments, but the magnitude and duration of the response depended on the composition of the added labile carbon mixture rather than the quantity of carbon added or the botanical origin of the peat. Treatments containing organic acids increased soil pH and altered other soil properties including redox potential but did not affect the activities of extracellular hydrolytic enzymes. CO2 but not CH4 production was found to be linearly related to microbial activity and redox potential. Our findings demonstrate the importance of root exudate composition in regulating greenhouse gas fluxes and propose that in situ plant species changes, particularly those associated with land use change, may account for small scale spatial variation in CO2 and CH4 fluxes due to species specific root exudate compositions.